Biodiversity of mangrove aquatic fauna in Purworejo, Central Java, Indonesia - WIRYANTO WIRYANTO; SUNARTO SUNARTO; SLAMET MARDIYANTO RAHAYU (Society for Indonesian Biodiversity, 2017)
Wiryanto, Sunarto, Rahayu SM. 2017. Biodiversity of mangrove aquatic fauna in Purworejo, Central Java, Indonesia. Biodiversitas 18: 1344-1352. Mangrove areas have important roles of ecologic, socio-economic, and socio-culture in ecosystem. Mangrove areas in Purworejo go into degradation as an impact of illegal logging, fishpond area expansion, settlements expansion and extension of agriculture area. All of the activities will influence the communities’ structure of mangroves vegetation and aquatic fauna. The purposes of research are to observe (i) biodiversity of mangroves aquatic fauna; (ii) correlation between mangrove vegetation and aquatic fauna; and (iii) the influence of abiotic factors towards biotic condition in research sites. This research was conducted in June-September 2016 at 3 stations and was determined with purposive sampling method. The research stations are Gedangan (Station 1), Jatikontal (Station 2) and Ngentak (Station 3). Vegetation of mangrove and aquatic fauna were observed with method of line transect and sampling removal. Association between variables (vegetation and aquatic fauna) is analyzed with Pearson Correlation Test. Influence of abiotic factors (physics and chemicals) on biotic (vegetation and aquatic fauna) is analyzed with t-test and regression test. According to the research, 34 species of aquatic fauna are from mangroves area of Purworejo. Highest value of aquatic fauna is found in Station 3 (ID 2.50). Pearson correlation test between vegetation and aquatic fauna obtains r value of 0,104. The t-test results a significant difference (sig 0.000) between abiotic factors and biotic condition and shows the impact of changes on both. Further test with regression method also indicates a weak impact on changes on abiotic factors towards biotic condition (r2 0.032).